Implementasi Video Pembelajaran Berbasis Canva Pada Pembelajaran Sains Materi Rotasi Dan Revolusi Bumi - Amikratunnisyah Amikratunnisyah; Sedya Santosa (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Science learning currently emphasizes students to be able to master 21st century competencies. 21st century abilities as well as the demands of advancing science and technology education require teachers as educators to be able to generate creative ideas in designing teaching materials and teaching media needed. One application that teachers can use to help the learning process is a Canva-based animated learning video. This study aims to describe the implementation of science learning using Canva-based video media in class VI SDN Inpres Kala. The type of research used is qualitative research with descriptive methods. The data in this study were obtained from observations and interviews. The results showed that with the learning video, students felt a new atmosphere in learning, because so far their learning was only focused on thematic books. The use of the Canva application in making learning videos, in addition to producing videos that are interesting for students, is also easy for teachers to use.